In vitro analysis of differential expression of collagens, integrins, and growth factors in cultured human chondrocytes - Gößler, Ulrich; Bugert, Peter; Bieback, Karen; Sadick, Haneen; Baisch, Alexander; Hörmann, Karl; Riedel, Frank (Otolaryngology - head and neck surgery, 2006)
OBJECTIVES: Tissue engineering represents a promising method for the construction of autologous chondrogenic grafts for reconstructive surgery. In cultured chondrocytes, the dedifferentiation and proliferation of the cells are critical factors that influence the generation of transplants. The aim of our study was to find and characterize markers for cell proliferation and dedifferentiation in cultured chondrocytes., STUDY DESIGN AND SETTING: Human chondrocytes were isolated from septal cartilage and held in primary cell culture. Cells were harvested after 1, 6, and 21 days. The differentiation of the cells was investigated with bright-field microscopy, the expression patterns of various proteins using immunohistochemistry, and the expression of distinct genes with the microarray technique., RESULTS: The chondrocytes showed a strong proliferation. After 6 and 21 days, collagen 9 and 10 were downregulated; collagen 11 was activated. Collagen 1 and 2 were downregulated after 6 days but were reactivated after 21 days. Tumor growth factor β (TGF-β)1 was strongly expressed on days 1, 6, and 21, TGF-β2 was never expressed, and TGF-β3 and -β4 were upregulated from day 1 to day 21. The TGF-β receptor III was expressed on days 1, 6, and 21. Integrin β1, β5, and α5 were upregulated from day 1 to day 21; integrin β3 was downregulated., CONCLUSION AND SIGNIFICANCE: Collagens 3, 4, 8, 9, and 11 might be new markers for the dedifferentiation of chondrocytes. Collagen 2 might be a marker for the synthetic activity of the cells rather than the dedifferentiation. TGF-β3 and -β4 might influence the dedifferentiation, which is fortified by the expression of TGF-β receptor III. Integrin β1, β5, and α5 might be involved in signal transmission for the dedifferentiation., © 2006 American Academy of Otolaryngology-Head and Neck Surgery Foundation, Inc. All rights reserved.
Gesehen am 11.03.2022